Direct synthesis of dimethyl carbonate from CO2 and methanol in dual supercritical phases over YxFe1−xOδ catalysts. (April 2022) - Sun, Wen; Zheng, Lan; Wang, Yuqi; Jia, Weihua; Guo, Wenzhao; Liu, Zhiru; Ding, Xin; Wu, Le; Fang, Tao
Abstract: In this study, the dual supercritical phases were proposed and employed to facilitate the synthesis of dimethyl carbonate (DMC) from CO2 and methanol, which may improve the diffusion rate and contact opportunities of reactant molecules. Under the novel reaction conditions, the synthesis temperature was higher than the supercritical temperatures of each reactant (>239 °C), and the partial pressure for each reactant constituent was larger than its partial supercritical pressure (pCO2 > 7.4 MPa & pmethanol > 8.1 MPa), respectively. A series of Yx Fe1−x O δ -T catalysts with perovskite-structure were applied in the dual supercritical phases, whose surface properties, crystal phase, microstructure, acidic−basic amounts, and the concentration of oxygen vacancies were detected by BET, XRD, SEM, NH3 /CO2 -TPD, XPS and EPR, respectively. It was evident from the characterization results that the Y0.5 Fe0.5 O δ -850 catalyst possessed the largest acidic−basic amounts, which enabled its highest catalytic activity. The experimental results revealed that higher DMC yield could be achieved under the novel dual supercritical phases (240 °C, 16 MPa), and the increased DMC yield without stirring in the autoclave can be obtained in an impressive shorter reaction time of 3 h, surpassing it acquired at the regular synthesis time of 9 h with stirring during the reaction. Highlights: The experiments were carried out under the novel dual supercritical phases. Y0.5 Fe0.5 O δ -850 catalyst has sturdy structure and steady catalytic activity. Reaction rate and activation energy were calculated under the novel condition. Reaction process was effectively enhanced based on the recognized mechanism.